Communication Skills Training for Practitioners to Increase Patient Adherence to Home-Based Rehabilitation for Chronic Low Back Pain: Results of a Cluster Randomized Controlled Trial - Lonsdale, C.; Hall, A.; Murray, A.; Williams, G.; McDonough, S.; Ntoumanis, Nikos; Owen, K.; Schwarzer, R.; Parker, P.; Kolt, G.; Hurley, D. (W.B. Saunders Co., 2017)
Objective: To assess the effect of an intervention designed to enhance physiotherapists' communication skills on patients' adherence to recommendations regarding home-based rehabilitation for chronic low back pain. Design: Cluster randomized controlled trial. Setting: Publicly funded physiotherapy clinics. Participants: A sample (N=308) of physiotherapists (n=53) and patients with chronic low back pain (n=255; 54% female patients; mean age, 45.3y). Interventions: Patients received publicly funded individual physiotherapy care. In the control arm, care was delivered by a physiotherapist who had completed a 1-hour workshop on evidence-based chronic low back pain management. Patients in the experimental arm received care from physiotherapists who had also completed 8 hours of communication skills training. Main Outcome Measures: (1) Patient-reported adherence to their physiotherapists' recommendations regarding home-based rehabilitation measured at 1, 4, 12, and 24 weeks after the initial treatment session. (2) Pain and pain-related function measured at baseline and at 4, 12, and 24 weeks. Results: A linear mixed model analysis revealed that the experimental arm patients' ratings of adherence were higher than those of controls (overall mean difference, .41; 95% confidence interval, .10-.72; d=.28; P=.01). Moderation analyses revealed that men, regardless of the intervention, showed improvements in pain-related function over time. Only women in the experimental arm showed functional improvements; female controls showed little change in function over time. The Communication Style and Exercise Compliance in Physiotherapy intervention did not influence patients' pain, regardless of their sex. Conclusions: Communication skills training for physiotherapists had short-term positive effects on patient adherence. This training may provide a motivational basis for behavior change and could be a useful component in complex interventions to promote adherence. Communication skills training may also improve some clinical outcomes for women, but not for men.